Reflection of Classical Traditions in Fine Arts (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2023)
National works created on the basis of historical sources make a great contribution not only to raising the spirituality of our nation, but also to introducing its beautiful values to the whole world. In this regard, the First President of the Republic of Uzbekistan, Islam Karimov, noted the role of historical sources in the interpretation of works of art: "Living by lessons from history, knowing the truths of history gives strength to a person, equips him with the truth of life. "The youth who will take our place tomorrow should be armed with the truth of this history[1][1] A.Karimov.Ona yurtimiz baxtu iqboli va buyuk kelajagi yо‘lida xizmat qilish-eng oliy saodatdir. Toshkent-“О‘zbekiston”-2015. B.113.